Relationship between hepatic progenitor cell‐mediated liver regeneration and non‐parenchymal cells. Issue 12 (4th April 2016) - Kitade, Mitsuteru; Kaji, Kosuke; Yoshiji, Hitoshi
Abstract : Hepatic progenitor cells (HPCs) are thought to reside in the canals of Hering and can be activated and contribute to liver regeneration in response to liver injury by proliferating and differentiating towards both hepatocytes and biliary epithelial cells. In this setting, several cytokines, chemokines, and growth factors related to liver inflammation and other liver cells comprising the HPC niche, namely hepatic stellate cells (HSCs), play crucial roles in HPC activation and differentiation. In response to several types of liver injury, tumor necrosis factor‐like weak inducer of apoptosis (TWEAK) is secreted by several inflammatory cells, including monocytes, T lymphocytes, and macrophages, and acts as an initiator of the HPC niche and HSC activation. Following TWEAK‐induced activation of the HPC niche, fibroblast growth factor 7 and hepatocyte growth factor released from activated HSC play central roles in maintaining HPC proliferation. In contrast, HGF‐MET and Wnt3a‐β‐catenin signals are the predominant mediators of the hepatocyte differentiation of HPC, whereas epidermal growth factor receptor–NOTCH signaling controls HPC differentiation towards biliary epithelial cells. These signals are maintained exclusively by activated HSC and inflammatory cells surrounding HPC. Together, HSC and inflammatory cells surrounding HPC are responsible for the precise control of HPC proliferation and differentiation fate. In this review, we discuss recent progress in understanding of interactions between HPC and other liver cells in HPC‐mediated liver regeneration in the setting of liver inflammation.